Analysis the performance of signalized intersection by using sidra - Ahmad Faiz, Nasir (2012)
This paper presents assessment of qualitative road service at signalized intersection and the implication , to their performance especially the delay in terms the number of vehicles and level of service at the intersection. Improvement of the level of service at each intersection usually results in an improvement of the overall operating performance of the highway. An analysis procedure that provides for the determination of level of service at intersection is therefore an important tool for designers, operation personnel and policy makers. Factors that affect the level of services at signalized intersection include the flow and distribution of traffic, headway, saturation flow, the geometric characteristics, and the signalization system. Determining the traffic volume and traffic distribution is vital in this assessment in order to figure out the delays and level of services. According to Arahan Teknik Jalan 8/86, delay is the main factor of classifying a particular signalized intersection. Moreover, excessive delay that causes long queue length not only indicates the amount of lost travel time and fuel consumption, it is also a measure of the frustration and discomfort of vehicle users. Based on the result of the study, appropriate decision and optimization can be made regard to nature and degree of improvement possible or justified, if there is any. In a nutshell, cost and time can be reduced whereas safety can be increased if a signalized intersection is operating at a high level of effectiveness and efficiency.